Laser generation of proton beams for the production of short-lived positron emitting radioisotopes - Spencer, I; Ledingham, K; Singhal, R; McCanny, T; McKenna, P; Clark, E; Krushelnick, K; Zepf, M; Beg, F; Tatarakis, M; Dangor, A; Norreys, P; et al. (2001)
Protons of energies up to 37 MeV have been generated when ultra-intense lasers (up to 1020Wcm-2) interact with hydrogen containing solid targets. These protons can be used to induce nuclear reactions in secondary targets to produce β+-emitting nuclei of relevance to the nuclear medicine community, namely 11C and 13N via (p,n) and (p,α) reactions. Activities of the order of 200 kBq have been measured from a single laser pulse interacting with a thin solid target. The possibility of using ultra-intense lasers to produce commercial amounts of short-lived positron emitting sources for positron emission tomography (PET) is discussed. © 2001 Elsevier Science B.V. All rights reserved.